A photocatalytic composite material and its preparation method and application

By introducing nitrogen defects and -C≡N structures into graphite phase carbon nitride (g-C3N4) and doping metal ions to form a photocatalytic composite material, the problem of low photocatalytic efficiency of g-C3N4 is solved, and more efficient photocatalytic performance and a wider photoresponse range are achieved.

CN116496300BActive Publication Date: 2025-04-11YTTRIUM HYDROGEN (BEIJING) TECH CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202310368785.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-04-07
Publication Date
2025-04-11
Estimated Expiration
2043-04-07

AI Technical Summary

Technical Problem

In practical applications, due to the limitation of the pure phase, the graphite phase carbon nitride (g-C3N4) has fast charge carrier recombination, low surface area and limited absorption of visible light, resulting in limited photocatalytic efficiency.

Method used

Design a photocatalytic composite material to enhance the π electron delocalization of the material by introducing nitrogen defects and -C≡N structures and doping metal ions such as potassium ions, thereby improving the migration efficiency of light absorption and photogenerated electrons. The composite material forms a network structure with improved photocatalytic properties by reacting with aminobenzonitrile (ABN) and metal salt.

Benefits of technology

The photocatalytic efficiency of photocatalytic composite materials is significantly improved, including improving the degradation efficiency of photocatalytic hydrogen evolution and bisphenol A, broadening the photo response range, and improving the electron hole separation rate.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116496300B_ABST
    Figure CN116496300B_ABST
Patent Text Reader

Abstract

The present invention discloses a photocatalytic composite material and its preparation method and application. It relates to the technical field of photocatalytic materials. The above-mentioned photocatalytic composite material has a compound with a structural formula as shown in Formula I: Formula I In the photocatalytic composite material of the present invention, in its network structure, ‑C≡N, nitrogen defects and aromatic rings can enhance the π electron delocalization of the photocatalytic composite material, which is beneficial to enhance light absorption and rapid migration of photogenerated electrons; further, the photocatalytic composite material of the present invention can harvest more photons under visible light irradiation and inhibit the recombination of photogenerated carriers, thereby significantly improving the photodegradation of PHE and BPA. Further, the photocatalytic composite material of the present invention exhibits extremely high photocatalytic activity in the green light region.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of photocatalytic materials, and in particular to a photocatalytic composite material and a preparation method and application thereof. Background Art

[0002] In 1972, Fujishima and Honda discovered the photolysis reaction of water on a TiO2 semiconductor single crystal electrode and discovered the "Honda-Fujishima effect" of semiconductor materials, which really started the research on multiphase semiconductor photocatalysis and set off a wave of photocatalytic water decomposition to solve the energy crisis. Hydrogen, as a renewable and clean energy, plays an important role in this system. Hydrogen can be used in fuel cells and the chemical industry. The existing method of producing hydrogen is mainly to produce hydrogen by photolysis of water. Photolysis of water is an important way to convert solar energy into usable energy and an effective way to store solar energy. Since the performance of photolysis of water is directly affected by the photogenerated charge transfer, band gap structure and stability of the catalyst, the efficiency of hydrogen production by the existing method is not high. Therefore, designing a new type of efficient and environmentally friendly photocatalyst is the key to improving the efficiency of hydrogen production.

[0003] Graphitic carbon nitride (g-C3N4) is a conjugated polymer with a two-dimensional layer structure. Its properties are stable and similar to that of graphite. As a new type of metal-free polymer photocatalyst, g-C3N4 has the advantages of being green, economical, stable, and having good optical and electronic properties. It has received extensive attention in the field of photocatalysis. g-C3N4 can currently be used in the fields of photocatalytic degradation of pollutants, photocatalytic water splitting to produce hydrogen, photocatalytic reduction of CO2, and selective organic synthesis reactions. As a typical representative of graphene-like materials, g-C3N4 has a band gap of 2.7eV and can absorb visible light. Since its layers are connected by van der Waals forces, it has good chemical and thermodynamic stability. In addition, g-C3N4 is non-toxic, abundant in source, low in price, and simple to prepare. However, in practical applications, pure phase g-C3N4 itself has many shortcomings that affect the improvement of its photocatalytic performance, so g-C3N4 is limited by rapid charge carrier recombination, low surface area and limited absorption of visible light. In particular, g-C3N4 has a high electron-hole recombination rate, which severely limits its photocatalytic efficiency.

[0004] Therefore, it is urgent to find a composite material to improve the photocatalytic performance of g-C3N4, broaden the light response range and increase its electron-hole separation rate. Summary of the invention

[0005] The first technical problem to be solved by the present invention is:

[0006] Provided is a photocatalytic composite material.

[0007] The second technical problem to be solved by the present invention is:

[0008] A method for preparing the photocatalytic composite material is provided.

[0009] The third technical problem to be solved by the present invention is:

[0010] Application of the photocatalytic composite material.

[0011] In order to solve the first technical problem, the technical solution adopted by the present invention is:

[0012] A photocatalytic composite material, the material having a structural formula as shown in Formula I:

[0013] Formula I: ;

[0014] Wherein, R1 and R2 are independently selected from the structure shown in Formula II or Formula III:

[0015] Formula II: ;

[0016] Formula III: ;

[0017] wherein R3, R4 and R5 are independently selected from amino, alkyl-substituted amino, hydroxy-substituted amino or halogen-substituted amino;

[0018] Among them, R7, R8 and R 10 are independently selected from imino, alkyl-substituted imino, hydroxy-substituted imino or halogen-substituted imino;

[0019] Among them, R6, R9 and R 11 are independently selected from amino, alkyl-substituted amino, hydroxy-substituted amino or halogen-substituted amino;

[0020] Among them, R3, R6, R9 and R 11 Among them, at least one is selected from -NH-C≡N or X;

[0021] Wherein, X includes the following structure: ;

[0022] Wherein, M is a metal ion.

[0023] According to the embodiments of the present invention, one of the technical solutions has at least one of the following advantages or beneficial effects:

[0024] In the photocatalytic composite material of the present invention, in its network structure, -C≡N, nitrogen defects and aromatic rings can enhance the π electron delocalization of the photocatalytic composite material, which is beneficial to enhancing light absorption and the rapid migration of photogenerated electrons; further, the photocatalytic composite material of the present invention can harvest more photons under visible light irradiation and inhibit the recombination of photogenerated carriers, thereby significantly improving the photodegradation of PHE (photocatalytic hydrogen evolution) and BPA (bisphenol A); further, the photocatalytic composite material of the present invention exhibits extremely high photocatalytic activity in the green light region.

[0025] The photocatalytic composite material of the present invention has greatly improved photocatalytic performance compared to graphite phase carbon nitride. The photocatalytic composite material prepared by the present invention also broadens the light response range of the material and improves the electron-hole separation rate.

[0026] According to an embodiment of the present invention, the alkyl group in the alkyl-substituted amino group includes C 1-8 Alkyl and halogen substituted C 1-8 alkyl.

[0027] According to an embodiment of the present invention, the alkyl substituted imino group includes C 1-8 Alkyl and halogen substituted C 1-8 alkyl.

[0028] According to an embodiment of the present invention, M includes at least one of potassium ions, calcium ions, zinc ions, magnesium ions and sodium ions. For M in structure X, the metal ion M is doped into structure X by combining with the electronegativity of the N atom in the X structure. This enhances the light absorption of the photocatalytic composite material and the rapid migration of photogenerated electrons, thereby promoting the photocatalytic activity of the photocatalytic composite material.

[0029] According to an embodiment of the present invention, the metal ion M is doped into the structure X and also into the structure R. 10 middle.

[0030] According to an embodiment of the present invention, metal ions M are doped on amino groups and imino groups in the photocatalytic material.

[0031] According to an embodiment of the present invention, the structural formula of R1 is shown as Formula II; the structural formula of R2 is shown as Formula III; and the structural formula of R6 is shown as Formula X.

[0032] According to an embodiment of the present invention, the photocatalytic composite material has the following structure:

[0033] In this structure, nitrogen defects and -C≡N were introduced, and potassium ions were doped, which promoted the enhancement of the π electron delocalization of the composite material, enhanced the light absorption and the rapid migration of photogenerated electrons.

[0034] In order to solve the second technical problem, the technical solution adopted by the present invention is:

[0035] A method for preparing the photocatalytic composite material comprises the following steps:

[0036] S1: mixing a compound containing a carbon nitride structure and aminobenzonitrile, and calcining the mixture to obtain an intermediate product;

[0037] S2 Under a protective atmosphere, the intermediate product is mixed with a molten salt containing metal cations, and the mixture is calcined to obtain a photocatalytic composite material.

[0038] According to the embodiments of the present invention, one of the technical solutions has at least one of the following advantages or beneficial effects:

[0039] In the method for preparing the photocatalytic composite material of the present invention, a compound containing a carbon nitride structure and aminobenzonitrile (ABN) undergo a Schiff base reaction to obtain the photocatalytic composite material in which aminobenzonitrile (ABN) is grafted onto tri-s-triazine. In step S2, nitrogen defects and -C≡N are introduced and metal cations are incorporated therein under the calcination reaction of the intermediate product with a molten salt containing metal cations, thereby enhancing the delocalization of the product.

[0040] The method for preparing the photocatalytic composite material of the present invention utilizes a high-temperature two-step thermal polymerization method to graft the visible light responsive aminobenzonitrile (ABN) onto the CN network structure to obtain the photocatalytic composite material. The method of the present invention has the advantages of simple operation, high reaction efficiency and good performance of the prepared material.

[0041] In the method of the present invention, an organic monomer aminobenzonitrile (ABN) is introduced into the graphite phase carbon nitride (g-C3N4) structure by reacting a compound containing a carbon nitride structure with aminobenzonitrile, so that aminobenzonitrile (ABN) is grafted onto the carbon nitride network structure. In the network structure, -C≡N, nitrogen defects, and aromatic rings in the aminobenzonitrile (ABN) structure can enhance the π electron delocalization of the photocatalytic composite material, which is beneficial to enhance light absorption and rapid migration of photogenerated electrons.

[0042] According to one embodiment of the present invention, the mass ratio of the compound containing a carbon nitride structure to the aminobenzonitrile is 100-400:4-5. The difference in the mass ratio of the compound containing a carbon nitride structure to the aminobenzonitrile will affect the structure of the photocatalytic composite material, thereby affecting the photocatalytic efficiency, hydrogen production yield and catalytic stability of the photocatalytic composite material.

[0043] According to one embodiment of the present invention, the mass ratio of the compound containing a carbon nitride structure to the aminobenzonitrile includes any of the following mass ratios: 100:4-5, 150:4-5, 200:4-5, 250:4-5, 300:4-5, 350:4-5, 400:4-5, 200:4, 200:4.5 and 200:5.

[0044] According to one embodiment of the present invention, the mass ratio of the aminobenzonitrile to the molten salt containing metal cations is 4-5:4-12.

[0045] According to one embodiment of the present invention, the mass ratio of the compound containing a carbon nitride structure to the aminobenzonitrile includes any of the following mass ratios: 4.5:4-12, 5:4-12, 4-5:4, 4-5:4.5, 4-5:5, 4-5:5.5, 4-5:6, 4-5:6.5, 4-5:7, 4-5:7.5, 4-5:8, 4-5:8.5, 4-5:9, 4-5:9.5, 4-5:10, 4-5:10.5, 4-5:11, 4-5:11.5, 4-5:12, 4:6 and 5:6.

[0046] According to one embodiment of the present invention, the compound containing a carbon nitride structure includes dicyandiamide.

[0047] According to one embodiment of the present invention, the aminobenzonitrile (ABN) accounts for 2% to 2.5% by mass in the raw materials of the photocatalytic composite material. The different mass proportions of the aminobenzonitrile (ABN) in the photocatalytic composite material will affect the structure of the photocatalytic composite material, thereby affecting the photocatalytic efficiency, hydrogen production yield and catalytic stability of the photocatalytic composite material.

[0048] According to one embodiment of the present invention, in step S1, a compound containing a carbon nitride structure can also be prepared by a polymerization reaction. Furthermore, the polymerization reaction is a thermal shrinkage polymerization method. The thermal shrinkage polymerization method is to prepare g-C3N4 by pyrolysis of a nitrogen-rich precursor. This method has the characteristics of cheap raw materials, simple preparation process, and good product crystal form.

[0049] According to one embodiment of the present invention, step S1 further comprises heating the nitrogen-containing organic matter to obtain a compound containing a carbon nitride structure through a polymerization reaction, wherein the compound containing a carbon nitride structure has a tri-s-triazine structural unit.

[0050] According to one embodiment of the present invention, the molten salt containing metal cations comprises at least one of a melt of an alkali metal and a melt of an alkaline earth metal halide. The metal ions in the molten salt containing metal cations act as charge compensators in the reaction of step S2 to balance the missing H in NH3 during the thermal polymerization of the molten salt, by balancing the CN - - The charge of C is introduced into the metal ions, that is, the metal ions are combined with the electronegativity of the N atoms, and are thus doped into the photocatalytic composite material.

[0051] According to one embodiment of the present invention, the molten salt containing metal cations includes NaCl-KCl molten salt, wherein the mass ratio of NaCl to KCl is 4.28-6.28:1.72-5.72. The mass ratio of the molten salt is to ensure the reaction. Different molten salts will affect the structure of the product. In addition, changes in the proportion of the molten salt and the type of the molten salt will also affect the reaction conditions.

[0052] According to one embodiment of the present invention, in step S1, the calcination temperature is 400-500°C, and in step S2, the calcination temperature is 600-700°C.

[0053] According to one embodiment of the present invention, in step S1, the calcination temperature is selected from any one of the following temperatures or a temperature range consisting of any two of the following temperatures: 400°C, 450°C, 500°C.

[0054] According to one embodiment of the present invention, in step S2, the calcination temperature is selected from any one of the following temperatures or a temperature range consisting of any two of the following temperatures: 600°C, 650°C, 700°C.

[0055] According to one embodiment of the present invention, in step S1, the calcination time is 2-4 hours, and in step S2, the calcination time is 2-4 hours.

[0056] According to one embodiment of the present invention, in step S1, the calcination time is selected from any one of the following time periods or a time interval consisting of any two of the following time periods: 2 hours, 2.5 hours, 3 hours, 3.5 hours and 4 hours.

[0057] According to one embodiment of the present invention, in step S2, the calcination time is selected from any one of the following time periods or a time interval consisting of any two of the following time periods: 2 hours, 2.5 hours, 3 hours, 3.5 hours and 4 hours.

[0058] According to an embodiment of the present invention, when the calcination temperature in step S1 is different from the calcination temperature in step S2, both are required to have the same calcination time.

[0059] According to one embodiment of the present invention, step S1 further includes cooling the intermediate product and then grinding it. The ground reactant is subjected to thermal polymerization in step S2, and the reaction will be more complete.

[0060] According to one embodiment of the present invention, step S2 further includes washing the calcined product with hot water and drying it.

[0061] According to one embodiment of the present invention, the drying step comprises the step of placing the product in a vacuum drying oven and drying it for 2-4 hours.

[0062] Another aspect of the present invention also relates to the application of the photocatalytic composite material in a hydrogen production device, including the photocatalytic composite material as described in the first embodiment. Since the application adopts all the technical solutions of the photocatalytic composite material, it has at least all the beneficial effects brought by the technical solutions of the above embodiments.

[0063] Another aspect of the present invention also relates to the application of the photocatalytic composite material in the degradation of bisphenol A and the photolysis of water to produce hydrogen under visible light. It includes the photocatalytic composite material as described in the first embodiment above. Since the application adopts all the technical solutions of the photocatalytic composite material of the above embodiment, it has at least all the beneficial effects brought by the technical solutions of the above embodiment.

[0064] Other features and advantages of the present invention will be set forth in the description which follows, and in part will be apparent from the description, or may be learned by practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0065] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:

[0066] Figure 1 Schematic diagram of the process for preparing the photocatalytic composite material in Example 1.

[0067] Figure 2 The UV-visible diffuse reflectance spectra of the photocatalytic composite materials obtained in Examples 1-3 and Comparative Examples 1-3 are shown.

[0068] Figure 3 This is a test graph of the photocatalytic hydrogen production rate of the photocatalytic composite materials obtained in Examples 1-3 and Comparative Examples 1-3.

[0069] Figure 4 The photocatalytic degradation curves of the samples obtained in Examples 1-3 and Comparative Examples 1-3 are shown.

[0070] Figure 5The photoluminescence spectra of the samples obtained in Examples 1-3 and Comparative Examples 1-3 are shown.

[0071] Figure 6 This is a photocatalytic stability test diagram of the sample obtained in Example 2.

[0072] Figure 7 The NMR spectrum of the sample obtained in Example 2 is shown in FIG. DETAILED DESCRIPTION

[0073] In the description of the present invention, if there is a description of first, second, etc., it is only for the purpose of distinguishing technical features, and cannot be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features or implicitly indicating the order of the indicated technical features.

[0074] The words "preferably", "more preferably", etc. in the present invention refer to embodiments of the present invention that may provide certain beneficial effects in certain circumstances. However, other embodiments may also be preferred under the same circumstances or other circumstances. In addition, the description of one or more preferred embodiments does not imply that other embodiments are not applicable, nor is it intended to exclude other embodiments from the scope of the present invention.

[0075] When a numerical range is disclosed herein, the above range is considered to be continuous and includes the minimum and maximum values ​​of the range, as well as every value between such minimum and maximum values. Further, when a range refers to an integer, every integer between the minimum and maximum values ​​of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be combined. In other words, unless otherwise indicated, all ranges disclosed herein should be understood to include any and all subranges included therein.

[0076] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of the present invention.

[0077] Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.

[0078] In the embodiments, the term "alkyl" refers to a saturated hydrocarbon containing a primary (normal) carbon atom, a secondary carbon atom, a tertiary carbon atom, a quaternary carbon atom, or a combination thereof. Phrases containing this term, such as "C 1-8"Alkyl" refers to an alkyl group containing 1 to 8 carbon atoms. Suitable examples include, but are not limited to, methyl (Me, -CH3), ethyl (Et, -CH2CH3), 1-propyl (n-Pr, n-propyl, -CH2CH2CH), 2-propyl (i-Pr, i-propyl, -CH(CH3)2), 1-butyl (n-Bu, n-butyl, -CH2CH2CH2CH3), 2-methyl-1-propyl (i-Bu, i-butyl, -CH2CH(CH3)2), 2-butyl (s-Bu, s-butyl, -CH(CH3)CH2CH3), 2-methyl-2-propyl (t-Bu, t-butyl, -C(CH3)3 ), 1-pentyl (n-pentyl, -CH2CH2CH2CH2CH3), 2-pentyl (-CH(CH3)CH2CH2CH3), 3-pentyl (-CH(CH2CH3)2), 2-methyl-2-butyl (-C(CH3)2CH2CH3), 3-methyl-2-butyl (-CH(CH3)CH (CH3)2), 3-methyl-1-butyl (-CH2CH2CH(CH3)2), 2-methyl-1-butyl (-CH2CH(CH3)CH2CH3), 1-hexyl (-CH2CH2CH2CH2CH2CH3), 2-hexyl (-CH(CH3)CH2CH2CH2CH3), 3-hexyl (-CH(CH2CH3)(CH2CH2CH3)), 2-methyl-2-pentyl (-C(CH3)2CH2CH2CH3), 3-methyl-2-pentyl (-CH(CH3)CH(CH3)CH2CH3), 4-methyl-2-pentyl (-CH(CH3)CH2CH(CH3)2), 3-methyl-3-pentyl (-C(CH3) (CH2CH3)2), 2-methyl-3-pentyl (-CH(CH2CH3)CH(CH3)2), 2 ,3-dimethyl-2-butyl (-C(CH3)2CH(CH3)2), 3,3-dimethyl-2-butyl (-CH(CH3) C(CH3)3 and octyl (-(CH2)7CH3).

[0079] In the embodiment, “C 1~10 "Alkyl" refers to an alkyl group having 1 to 10 carbon atoms, and means a saturated aliphatic hydrocarbon group including a branched or straight chain having a specified number of carbon atoms. For example, C1~ 10 , such as in "C1~ 10 "Alkyl" is defined as including groups having 1, 2, 3, 4, 5, 6, 7, 8, 9 or 10 carbon atoms in a straight or branched structure. For example, "C1- 10 The term "alkyl" specifically includes methyl, ethyl, n-propyl, isopropyl, n-butyl, tert-butyl, isobutyl, pentyl, hexyl, heptyl, octyl, nonyl and decyl.

[0080] In the embodiment, “C 1~4 The term "alkyl" refers to an alkyl group having 1 to 4 carbon atoms, such as methyl, ethyl, propyl, isopropyl, n-butyl, isobutyl or tert-butyl.

[0081] In the embodiment, "C1~ 10 "Alkoxy" means an alkyl group as defined above connected via an oxygen atom, such as methoxy, ethoxy, n-propoxy, isopropoxy, n-butoxy, isobutoxy or tert-butoxy. Similarly, "C1- 10 "Haloalkyl" refers to an alkyl group as defined above substituted with a halogen.

[0082] In the embodiments, "alkenyl" refers to a group having at least one unsaturated site, i.e., a carbon-carbon sp 2 A hydrocarbon containing a positive, secondary, tertiary, or cyclic carbon atom with a double bond. Phrases containing this term, such as "C 2-8 "Alkenyl" refers to an alkenyl group containing 2 to 8 carbon atoms. Suitable examples include, but are not limited to, ethenyl (-CH=CH2), propenyl (-CH2CH=CH2), cyclopentenyl (-C5H7) and 5-hexenyl (-CH2CH2CH2CH2CH=CH2).

[0083] In the examples, "halogen" or "halo" refers to F, Cl, Br or I.

[0084] In the embodiments, "halogen substituted" means that any number of H at any selected position on the corresponding group is substituted by halogen, such as fluoromethyl, including monofluoromethyl, difluoromethyl, trifluoromethyl.

[0085] Example 1

[0086] A method for preparing a photocatalytic composite material, such as Figure 1 Specifically, the following steps are included:

[0087] (1) Weigh 4 g of dicyandiamide and 80 mg of aminobenzonitrile (ABN) and mix and grind them evenly. Then transfer the mixture into a 100 mL alumina crucible with a lid and calcine it at 500 °C in a muffle furnace for 2 h.

[0088] (2) The obtained solid powder and 6.0 g of metal salt (4.28 g NaCl and 1.72 g KCl) were ground for 20 min and then calcined at 610 °C in a nitrogen-filled tube furnace for 2 h.

[0089] (3) After cooling naturally to room temperature, the mixture was thoroughly washed with deionized water and dried in a vacuum oven.

[0090] A photocatalytic composite material was prepared through the above steps, and the sample was named DCN-NaK-80ABN.

[0091] like Figure 1 As shown, dicyandiamide can obtain g-C3N4 through polymerization reaction, and g-C3N4 has the structural unit of tri-s-triazine.

[0092] Among them, the aminobenzonitrile (ABN) obtained by Schiff base reaction of dicyandiamide and aminobenzonitrile (ABN) is grafted on the structural unit of tri-s-triazine, which is a photocatalytic composite material. The photocatalytic composite material can further repeat the above reaction to obtain a new aminobenzonitrile (ABN) grafted on the structural unit of tri-s-triazine, that is, a new photocatalytic composite material is obtained; when other substances with tri-s-triazine structure are further added, the photocatalytic composite material can further repeat the above reaction to obtain a new aminobenzonitrile (ABN) grafted on the structural unit of tri-s-triazine, that is, a new photocatalytic composite material is obtained. When the material is ground and calcined with 6.0 g of metal salt (4.28 g NaCl and 1.72 g KCl) in the second step, K / Na ions are introduced into the material as charge compensators to balance the missing H in NH3 in the molten salt thermal polymerization, and the eutectic NaCl-KCl salt will cause nitrogen defects and -C≡N. Finally, a high-performance photocatalytic composite material with enhanced delocalization and containing -C≡N and nitrogen defects can be obtained.

[0093] The photocatalytic composite material prepared in Example 1 has the structural formula:

[0094] .

[0095] Example 2

[0096] A method for preparing a photocatalytic composite material comprises the following steps:

[0097] (1) Weigh 4 g of dicyandiamide and 90 mg of aminobenzonitrile (ABN) and mix and grind them evenly. Then transfer the mixture into a 100 mL alumina crucible with a lid and calcine it at 500 °C in a muffle furnace for 2 h.

[0098] (2) The obtained solid powder and 6.0 g of metal salt (4.28 g NaCl and 1.72 g KCl) were ground for 20 min and then calcined at 610 °C in a nitrogen-filled tube furnace for 2 h.

[0099] (3) After cooling naturally to room temperature, the mixture was thoroughly washed with deionized water and dried in a vacuum oven.

[0100] A photocatalytic composite material was prepared through the above steps, and the sample was named DCN-NaK-90ABN.

[0101] Compared with Example 1, the only difference is that the added amount of aminobenzonitrile (ABN) is 90 mg, and the prepared sample is named DCN-NaK-90ABN.

[0102] Example 3

[0103] A method for preparing a photocatalytic composite material comprises the following steps:

[0104] (1) Weigh 4 g of dicyandiamide and 100 mg of aminobenzonitrile (ABN), mix and grind them evenly, then transfer the mixture into a 100 mL alumina crucible with a lid and calcine it at 500 °C in a muffle furnace for 2 h;

[0105] (2) The obtained solid powder and 6.0 g of metal salt (4.28 g NaCl and 1.72 g KCl) were ground for 20 min and then calcined at 610 °C in a nitrogen-filled tube furnace for 2 h.

[0106] (3) After cooling naturally to room temperature, the mixture was thoroughly washed with deionized water and dried in a vacuum oven.

[0107] A photocatalytic composite material was prepared through the above steps, and the sample was named DCN-NaK-100ABN.

[0108] Compared with Example 1, the only difference is that the added amount of aminobenzonitrile (ABN) is 100 mg, and the prepared sample is named DCN-NaK-100ABN.

[0109] The only difference between Examples 1-3 is the amount of aminobenzonitrile (ABN) added. The present invention grafts aminobenzonitrile (ABN) onto a g-C3N4 network structure and performs a second step calcination treatment under a molten salt environment to obtain the above-mentioned photocatalytic composite material of the present invention. Due to the different amounts of aminobenzonitrile (ABN) added, the resulting material has different proportions of aminobenzonitrile (ABN) in the composite material of the CN network, which leads to certain differences in its chemical properties and catalytic efficiency. By adjusting the ratio of dicyandiamide and aminobenzonitrile (ABN), changes in the aminobenzonitrile (ABN) in the g-C3N4 network structure in the final polymer are caused, thereby obtaining photocatalytic composite materials at different ratios.

[0110] Example 4

[0111] A photocatalytic composite material, the material having a compound of the structural formula shown in Formula I:

[0112] Formula I: ;

[0113] Wherein, R1 is the structure shown in formula II;

[0114] Wherein, R2 is the structure shown in formula III:

[0115] Formula II: ;

[0116] Formula III: ;

[0117] Wherein, R3 is -NHCl;

[0118] Wherein, R4 is an amino group;

[0119] Wherein, R5 is an amino group;

[0120] Wherein, R6 is -NH-C≡N;

[0121] Wherein, R7 is an imino group;

[0122] Wherein, R8 is an imino group;

[0123] Wherein, R9 is an imino group;

[0124] Among them, R 10 is an imino group;

[0125] Among them, R 11 is X;

[0126] Wherein, X includes the following structure: ;

[0127] Wherein, M is a potassium ion.

[0128] Example 5

[0129] A photocatalytic composite material, the material having a compound of the structural formula shown in Formula I:

[0130] Formula I: ;

[0131] Wherein, R1 and R2 are structures shown in formula III:

[0132] Formula III: ;

[0133] Wherein, R6 is -NH-C≡N;

[0134] Wherein, R7 is an imino group;

[0135] Wherein, R8 is an imino group;

[0136] Wherein, R9 is an imino group;

[0137] Among them, R 10 is an imino group;

[0138] Among them, R11 is X;

[0139] Wherein, X includes the following structure: ;

[0140] Wherein, M is a sodium ion.

[0141] Example 6

[0142] A photocatalytic composite material, the material having a compound of the structural formula shown in Formula I:

[0143] Formula I: ;

[0144] Wherein, R1 is the structure shown in formula II;

[0145] Wherein, R2 is the structure shown in formula III:

[0146] Formula II: ;

[0147] Formula III: ;

[0148] Wherein, R3 is an amino group;

[0149] Wherein, R4 is an amino group;

[0150] Wherein, R5 is an amino group;

[0151] Wherein, R6 is X;

[0152] Wherein, R7 is an imino group;

[0153] Wherein, R8 is an imino group;

[0154] Wherein, R9 is -NH-C≡N;

[0155] Among them, R 10 is an imino group;

[0156] Among them, R 11 is X;

[0157] Wherein, X includes the following structure: ;

[0158] Wherein, M is a potassium ion.

[0159] Comparative Example 1

[0160] A method for preparing a pure phase g-C3N4 photocatalyst comprises the following steps:

[0161] Weigh 4 g of dicyandiamide, grind it evenly, and place it in a 100 ml alumina crucible with a lid. Then place the crucible in a muffle furnace, gradually heat it to 610°C at a heating rate of 5°C / min, and then keep it at 610°C for 2 h; cool it naturally to room temperature, and grind the obtained sample again thoroughly.

[0162] Compared with Example 2, the difference is that aminobenzonitrile (ABN) and 6.0 g of metal salt (4.28 g NaCl and 1.72 g KCl) are not added, and the prepared sample is named DCN.

[0163] Comparative Example 2

[0164] A method for preparing a photocatalytic composite material comprises the following steps:

[0165] (1) Weigh 4 g of dicyandiamide and 90 mg of aminobenzonitrile (ABN) and mix and grind them evenly. Then transfer the mixture into a 100 mL alumina crucible with a lid and calcine it at 500 °C in a muffle furnace for 2 h.

[0166] (2) The obtained solid powder was ground for 20 min and then calcined at 610 °C for 2 h in a nitrogen-filled tube furnace;

[0167] (3) Cool naturally to room temperature, grind and collect for processing.

[0168] A photocatalytic composite material was prepared through the above steps, and the sample was named DCN-90ABN.

[0169] Compared with Example 2, the only difference is that 6.0 g of metal salt (4.28 g NaCl and 1.72 g KCl) is not added and the water washing and drying process is not performed. The prepared sample is named DCN-90ABN.

[0170] Comparative Example 3

[0171] A method for preparing a photocatalytic composite material comprises the following steps:

[0172] (1) Weigh 4 g of dicyandiamide and grind it evenly. Then transfer it to a 100 mL alumina crucible with a lid and calcine it at 500 °C in a muffle furnace for 2 h.

[0173] (2) The obtained solid powder and 6.0 g of metal salt (4.28 g NaCl and 1.72 g KCl) were ground for 20 min and then calcined at 610 °C in a nitrogen-filled tube furnace for 2 h.

[0174] (3) After cooling naturally to room temperature, the mixture was thoroughly washed with deionized water and dried in a vacuum oven.

[0175] A photocatalytic composite material was prepared through the above steps, and the sample was named DCN-NaK.

[0176] Compared with Example 2, the only difference is that 90 mg of aminobenzonitrile (ABN) is not added, and the prepared sample is named DCN-NaK.

[0177] Performance Test:

[0178] Test Example 1:

[0179] UV-Vis diffuse reflectance experiment:

[0180] The photocatalytic composite materials obtained in Examples 1-3 and Comparative Examples 1-3 were subjected to UV-visible diffuse reflectance spectroscopy to test the following: Figure 2 shown.

[0181] The instrument used for UV-visible diffuse reflectance spectroscopy testing is Hitachi U-3010 UV–visspectrometer, and BaSO4 is used as a reference.

[0182] Depend on Figure 2 It can be seen that, obviously, with the increase of ABN loading, the light absorption of DCN-NaK-xABN gradually increases between 460 nm and 700 nm, which is due to the improvement of grafted benzene rings and delocalization. The enhanced optical absorption of the sample indicates that there are stable electrons and holes in the excited state, indicating that photochemistry may be utilized even under conditions of wavelengths greater than 500 nm. The color of the sample gradually deepens, from the light yellow of DCN to the bright yellow of DCN-NaK, and then to the brownish yellow of DCN- NaK-90ABN. The absorption range of visible light of the photocatalytic composite material prepared by the present invention gradually widens, which will greatly benefit the improvement of the photocatalytic hydrogen production performance of the material.

[0183] Test Example 2:

[0184] Photocatalytic hydrogen production rate experiment:

[0185] The specific experimental conditions and methods are as follows: using the Labsolar-6A photocatalytic online analysis system of Beijing Perfect Light Technology Co., Ltd.

[0186] The specific reaction solution is as follows: 50 mg of the photocatalytic composite material is added to 100 mL of an aqueous solution containing 10 mL of a sacrificial agent, triethanolamine, and 3 wt% of Pt is used as a co-catalyst. The light source is PLS-SXE 300 / 300UV, and the light intensity is 100 mW / cm 2 ,λ>420nm.

[0187] The photocatalytic hydrogen production rates of the photocatalytic composite materials obtained in Examples 1-3 and Comparative Examples 1-3 were tested under the above experimental conditions and methods. The results are as follows: Figure 3 As shown, Figure 3 (a) is a test graph of hydrogen production rate at a wavelength of about 420nm. Figure 3 (b) is a test graph of hydrogen production rate at wavelengths of 500nm, 550nm and 600nm.

[0188] Depend on Figure 3 It can be seen that compared with the original sample DCN (the material prepared in the comparative example), almost all g-C3N4 composite materials grafted with aminobenzonitrile (ABN) under NaCl-KCl molten salt: DCN-NaK-xABN have obvious improvement in photocatalytic hydrogen production performance.

[0189] Specifically, the hydrogen production rate of the DCN sample prepared in Comparative Example 1 is 30 μmol h -1 g -1 , which is significantly lower than the 210 μmol h of DCN-NaK-90ABN prepared in Example 2. -1 g -1 ;

[0190] The hydrogen production rate of DCN-NaK-80ABN prepared in Example 1 was 177 μmol h -1 g -1 , which is lower than the DCN-NaK-90ABN prepared in Example 2;

[0191] The hydrogen production rate of DCN-NaK-100ABN prepared in Example 3 was 154 μmol h -1 g -1 , which is lower than the DCN-NaK-90ABN prepared in Example 2;

[0192] More importantly, at long wavelengths of 500 nm and 550 nm, DCN-NaK-xABN still exhibits excellent hydrogen evolution performance.

[0193] Specifically, the hydrogen production rate of the DCN sample prepared in the comparative example at 500 nm was only 4 µmol h -1 g -1 , which is significantly lower than the hydrogen production rate of DCN-NaK-90ABN prepared in Example 2 at 500 nm of 44 μmol h -1 g -1 ; and the hydrogen production rate of DCN-NaK-90ABN at 550nm is still 25µmol h -1 g -1 At this time, DCN produces no hydrogen at 550nm.

[0194] The hydrogen production rate of DCN-90ABN prepared in Comparative Example 2 at 500 nm was 5 µmol h -1 g -1 , which is much lower than that of DCN-NaK-90ABN in Example 2. The hydrogen production rate of DCN-NaK prepared in Comparative Example 5 at 500 nm is 10 μmol h -1 g -1 , which is lower than the DCN-NaK-90ABN of Example 2. The sample DCN prepared in Comparative Example 1, the DCN-90ABN prepared in Comparative Example 2, and the DCN-NaK prepared in Comparative Example 3 are all higher than the DCN prepared in the Comparative Example.

[0195] In summary, the sample DCN-NaK-90ABN obtained by grafting an appropriate amount of aminobenzonitrile (ABN) onto the CN network structure with the assistance of NaCl-KCl molten salt has the highest photocatalytic hydrogen production performance, that is, the photocatalytic hydrogen production rate of the photocatalytic composite material prepared in Example 2 is the best. As the amount of aminobenzonitrile (ABN) is further increased, the hydrogen production performance of the prepared photocatalytic composite material sample will gradually decrease, which may be due to excessive doping, which will damage some properties of the semiconductor and affect the photocatalytic performance of the material.

[0196] Test Example 3:

[0197] Photocatalytic degradation of BPA experiment:

[0198] The specific experimental conditions and methods are as follows: the filtrate was analyzed by a high performance liquid chromatography system (HPLC) and a fluorescence detector (Waters e2695 Alliance, USA) at 245 nm.

[0199] Specifically, the reaction solution is as follows: 50 mg of the photocatalytic composite material is dispersed in 100 mL of BPA (bisphenol A) aqueous solution (20 mg L -1 ) and stirred continuously for 60 min to perform dark pre-adsorption experiments. The system was then exposed to irradiation with a 300 W xenon lamp (PLS-SXE300D, Beijing Perfectlight Technology Co., Ltd.) equipped with a 420 nm cutoff filter. 3 mL of the reaction solution (filtrate) was periodically extracted using a 0.45 µm membrane.

[0200] The photocatalytic degradation curves of the samples obtained in Examples 1-3 and Comparative Examples 1-3 were tested under the above experimental conditions and methods. The results are as follows: Figure 4 As shown, Figure 4 (a) is a test diagram of the degradation efficiency of the material for bisphenol A under visible light irradiation, including the adsorption process and the degradation of the material after adding visible light. Figure 4 (b) is a test diagram of the relationship between the irradiation time and the concentration at time t / initial concentration after adding different capture agents to Example 2. By adding different capture agents to Example 2, it is possible to determine which part of the material is mainly responsible for the degradation. For example, N2 is added to remove superoxide radicals in the material. Figure 4 (c) is a test diagram of the reaction rate constant (k) and k value reaction degradation difference of the kinetic data of photodegradation of the samples obtained in Examples 1-3 and Comparative Examples 1-3 according to pseudo first-order correlation fitting, Figure 4 (d) is a test graph showing the relationship between the irradiation time at a wavelength of 500 nm and the concentration at time t / initial concentration of the samples obtained in Examples 1-3 and Comparative Examples 1-3. Figure 4 df in is the kinetic-related reaction constant K after the wavelength is changed to 500nm and 550nm and the capture agent is added. Figure 4 (e) is a test graph of the relationship between the irradiation time at a wavelength of 550 nm and the concentration at time t / initial concentration of the samples obtained in Examples 1-3 and Comparative Examples 1-3, Figure 4 (f) is a test graph of the kinetic-related reaction constant K of the samples obtained in Examples 1-3 and Comparative Examples 1-3 after adding the capture agent.

[0201] from Figure 4It can be seen that the adsorption of BPA by all samples is weak (<4.5%), indicating that adsorption does not play a key role in photocatalysis. However, under visible light irradiation, DCN-NaK-xABN has significantly improved the removal efficiency of BPA compared with DCN. The photodegradation efficiencies of DCN-NaK-80ABN, DCN-NaK-90ABN and DCN-NaK-100ABN are 88.3%, 100% and 88.7%, respectively, which are much higher than DCN (only 5.6%), DCN-NaK (43.8%) and DCN-90ABN (5.1%), indicating that the formation defects and enhanced delocalization in DCN-NaK-xABN can effectively improve its photocatalytic activity. The significant improvement in photodegradation efficiency is due to the formation defects and enhanced delocalization and increased adsorption capacity in DCN-NaK-xABN. Moreover, the sample DCN-NaK-90ABN obtained by grafting an appropriate amount of aminobenzonitrile (ABN) onto the CN network structure has the highest photocatalytic degradation efficiency. In addition, the addition of aminobenzonitrile (ABN) enhances delocalization and significantly improves the optical absorption in the long wavelength range, which can effectively photodegrade BPA at 500 nm and 550 nm. It is obvious that the kinetic-related reaction rate constant (k) of the photodegradation of DCN-NaK-90ABN at 500 nm is 95, which is much higher than DCN (k=3), DCN-NaK (k=10), and DCN-90ABN (k=2); the kinetic-related reaction rate constant (k) of the photodegradation of DCN-NaK-90ABN at 550 nm is 62, which is still much higher than DCN (k=2), DCN-NaK (k=9), and DCN-90ABN (k=0.4).

[0202] In summary, the sample DCN-NaK-90ABN obtained by grafting an appropriate amount of aminobenzonitrile (ABN) onto the CN network structure with the assistance of NaCl-KCl molten salt has the highest photocatalytic degradation performance of BPA, that is, the photocatalytic degradation performance of the photocatalytic composite material prepared in Example 2 is the best. As the amount of aminobenzonitrile (ABN) is further increased, the degradation performance of the photocatalytic composite material sample prepared will gradually decrease, which further shows that the effective incorporation of aminobenzonitrile (ABN) monomer will make the sample DCN-NaK-90ABN obtained by the CN network structure have the highest photocatalytic degradation efficiency.

[0203] Test Example 4:

[0204] Photoluminescence spectrum test:

[0205] The specific experimental conditions are as follows: at room temperature, using a FLS-980 fluorescence spectrometer.

[0206] The photoluminescence spectra of the samples obtained in Examples 1-3 and Comparative Examples 1-3 are as follows: Figure 5 shown.

[0207] Depend on Figure 5 It can be seen that when using NaCl-KCl molten salt or ABN, the PL intensity is significantly reduced relative to DCN due to the generation defects (such as -C≡N and nitrogen defects) contained in DCN-NaK and the enhanced delocalization in DCN-90ABN. The significant attenuation of the peak intensity indicates the reduction of carrier recombination. In addition, the red shift of DCN-NaK and DCN-NaK-90ABN is from 462 nm to 498 nm and 533 nm, respectively, highlighting the improved stability of photogenerated electrons and holes. With the addition of aminobenzonitrile (ABN), the composite material obtained after aminobenzonitrile (ABN) is grafted onto the CN network structure can effectively promote the separation of photogenerated electrons and photogenerated holes in the sample. This is due to the enhancement of π electron delocalization and the rapid migration of photogenerated electrons as the organic monomer aminobenzonitrile (ABN) is grafted onto the CN network structure. Thereby inhibiting the rapid recombination of photogenerated holes and photogenerated electrons, and promoting the photocatalytic degradation and hydrogen production activity of the catalyst.

[0208] Test Example 5:

[0209] Photocatalytic stability experiment:

[0210] Example 2 The photocatalytic stability test of the sample DCN-NaK-90ABN obtained is as follows Figure 6 shown.

[0211] Depend on Figure 6 It can be seen that after 5 cycles of continuous illumination for 20 hours (the generated hydrogen is vacuumed out every 4 hours, which counts as one cycle), the hydrogen production activity of the sample DCN-NaK-90ABN has basically not decayed, proving that the catalyst has good stability and good application prospects in practical applications.

[0212] Test Example 6:

[0213] NMR spectroscopy experiments:

[0214] Nuclear magnetic resonance spectra of samples DCN-NaK and DCN-NaK-90ABN obtained in Example 2 Figure 7 shown.

[0215] from Figure 7 It can be observed that two typical characteristic peaks can be detected in DCN-NaK at 162.8 and 156.2 ppm, corresponding to the carbon atoms of melem (CN3, 1) and CN2(NHx)(2) in the heptazine unit, respectively. The chemical shift of DCN-NaK-90ABN is slightly shifted to the high field ( Figure 7, inset), which means improved electron delocalization. The peaks of DCN-NaK and DCN-NaK-xABN are at 168.0 and 111.0 ppm, respectively, which can be attributed to the formed -C≡N structure and adjacent carbon atoms. Based on these characterization results, the aromatic ring structure can be grafted into the CN framework by adding ABN. The use of eutectic NaCl-KCl salt leads to nitrogen defects and -C≡N. In addition, the aromatic rings in -C≡N and aminobenzonitrile (ABN) can enhance the π electron delocalization, which is beneficial to the enhancement of light absorption and the rapid migration of photogenerated electrons, promoting the photocatalytic hydrogen production activity of the catalyst.

[0216] The above are only embodiments of the present invention, and are not intended to limit the patent scope of the present invention. Any equivalent transformations made using the contents of the present invention specification, or directly or indirectly applied in related technical fields, are also included in the patent protection scope of the present invention.

Claims

1. A photocatalytic composite material, characterized in that: The structural formula of the photocatalytic composite material is as follows: The method for preparing the photocatalytic composite material comprises the following steps: S1 Weigh 4 g of dicyandiamide and 80 mg, 90 mg or 100 mg of aminobenzonitrile and mix and grind them evenly, then transfer the mixture into a 100 mL alumina crucible with a lid, and calcine at 500 ° C in a muffle furnace for 2 h to obtain an intermediate product; S2: The intermediate product was ground together with 4.28 g NaCl and 1.72 g KCl for 20 min, and then calcined at 610° C. for 2 h in a nitrogen-filled tubular furnace to obtain the photocatalytic composite material.

2. Use of the photocatalytic composite material as claimed in claim 1 in the degradation of bisphenol A or the photolysis of water to produce hydrogen under visible light.

Citation Information

Patent Citations

  • Preparation method and application of benzene ring grafted phosphorus-doped carbon nitride hollow nanotube photocatalyst

    CN117065797A

  • Photocatalytic material as well as preparation method and application thereof

    CN117225444A

  • Photocatalytic material as well as preparation method and application thereof

    CN117225453A

  • Photocatalytic material based on nitrogen carbide network structure as well as preparation method and application of photocatalytic material

    CN117380265A